Development of a goosegrass (Eleusine indica) draft genome and application to weed science research. Issue 10 (10th April 2019) - Zhang, Hui; Hall, Nathan; Goertzen, Leslie R; Bi, Bo; Chen, Charles Y; Peatman, Eric; Lowe, Elijah K; Patel, Jinesh; McElroy, Joseph S
Abstract: BACKGROUND: Genomes are vital to the study of genomics, population genetics, and evolution of species. To date, only one genome ( Echinochloa crus‐galli ) for C4 annual weedy grass species has been sequenced. Research was conducted to develop a draft genome of goosegrass ( Eleusine indica ; 2n = 2x = 18), one of the most common and troublesome weeds in the world. RESULTS: A draft assembly of an approximately 492 Mb whole‐genome sequence of goosegrass was obtained by de novo assembly of paired‐end and mate‐paired reads generated by Illumina sequencing of total genomic DNA. The genome was assembled into 24, 072 scaffolds with N50 = 233, 459 bp. More than 99% of transcriptome sequences were mapped to the goosegrass draft genome, and 95% of the commonly conserved plant genes were present. The assembled genome contains 25, 467 unique protein‐coding genes. Genes associated with herbicide resistance were obtained and variant calling allowed the detection of 754, 409 single nucleotide polymorphisms. In addition, we also report 115, 417 simple sequence repeats which can be deployed in population genetics and phylogenetic analysis. CONCLUSION: This is the first report of genome sequence of goosegrass. Our assembly was able to identify all major herbicide‐resistance related genes and develop a useful tool for other genomic and evolutionary analysis. © 2019 Society of Chemical Industry Abstract : Goosegrass genome was assembled and genes associated with herbicide resistance were obtained from this genome. The draft genome can aid in understanding weed evolution and herbicide resistance.